Secondary structure as a conformational determinant in processing of peptide precursors at dibasic amino acids. Issue 1 (2003) - Lazar Lazar, Noureddine Noureddine; Brakch Brakch, Noureddine Noureddine; Panchal Panchal, Maï Maï; Cohen Cohen, Paul Paul; Rholam Rholam, Mohamed Mohamed
Abstract : The aim of this work was to establish the functional role of selected secondary structure motifs of peptide hormone precursors in their selective recognition by the corresponding converting endoproteases. The strategy was based on the use of synthetic peptides either reproducing or mimicking the sequences of the cleavage regions of two distinct models; i.e. pro‒ocytocin–neurophysin and prosomatostatin. Both prohormones were capable to release their biologically active sequences either by cleavage at a dibasic stretch or by proteolysis at a monobasic site. Both kinetic and thermodynamic parameters of peptide cleavage by various convertases were measured. They were examined in light of structural data on preferred conformations adopted by these substrates, which were obtained by a combination of spectroscopical techniques including CD, FT‒IR and proton NMR. In the case of prosomatostatin, these approaches were in addition paralleled by site‒directed mutagenesis experiments. The wealth of collected data point toward the conclusion that β ‒turns and/or loops, favored by sequences bearing basic residues, constitute a key feature in the specification of those peptide loci which are proteolytically processed in vivo . They will be discussed with respect of other processing mechanisms where these mechanisms were also shown.